The Cardiovascular Conundrum in Ethnic and Sexual Minorities: A Potential Biomarker of Constant Coping With Discrimination - Rosati, Fausta; Williams, DeWayne P.; Juster, Robert-Paul; Thayer, Julian F.; Ottaviani, Cristina; Baiocco, Roberto (Frontiers in Neuroscience, 2021)
Background: A paradoxical profile of greater elevated sympathetic vasoconstriction (increased total peripheral resistance, TPR) and increased vagally-mediated heart rate variability (HRV) -the so-called Cardiovascular Conundrum- has been reported in African Americans (AAs) both at rest and in response to orthostasis. Whereas some authors have attributed this pattern to genetic factors, others have pointed to the potential role of coping with repeated racial discrimination. Objective: To disentangle between these alternative explanations, we have examined the hemodynamic profile of another population that is likely to be exposed to episodes of discrimination, i.e., sexual minorities. Methods: The first study was conducted on a sample of AAs and European Americans (EAs) with the aim of replicating previous results on the Cardiovascular Conundrum. In the second study, lesbian, gay, and bisexual (LGB) people, matched by age and sex with heterosexual participants, underwent a hemodynamic and autonomic assessment at rest and during an emotional (in the experimental group, both LGB-related and non LGB related), and a cognitive stressor. Results: The first study confirmed a pattern of higher resting HRV, paired with higher TPR, in AAs compared to EAs. In the second study, compared to heterosexuals, the LGB group showed the Cardiovascular Conundrum pattern, characterized by greater HRV and higher TPR at baseline and a more vascular hemodynamic profile and prominent compensation deficit in response to both tasks, and particularly during the LGB-related emotional task. However, in LGB only, the vascular response was negatively correlated with perceived discrimination. Conclusion: Present preliminary results are discussed in terms of maladaptive physiological consequences of exposure to chronic stress and the chronic use of dysfunctional emotion regulation strategies such as suppression.